Non-stipendiary ministry in the Church of England: a history of the development of an idea - Vaughan, Patrick H. (1987)
This thesis traces the development of the idea of non-stipendiary ministry (NSM) in the Church of England from 1833, when it was first mooted by Thomas Arnold, to the present day. Four phases of development are identified and examined: first, the nineteenth century, when proposals to open the diaconate to men in secular employment were under discussion; second, the period leading up to the major discussion of the idea at the Lambeth Conference of 1930; third, the period leading up to the institutional establishment of 'Auxiliary Pastoral Ministry' in 1970; and fourth, the subsequent period of growth and development of NSM in practice. The method adopted is to analyse relevant debates in Convocation, Church Assembly and General Synod, together with relevant published material; new unpublished material from archives in Brisbane Diocese, Church House, Westminster, Lambeth Palace, and Selly Oak Library, as well as from the private papers of Roland Allen, is presented and analysed; the influence of developments in Anglican Churches overseas, of the World Council of Churches and of the French Worker-Priest Movement is assessed; the influence of certain key figures is examined, including that of Thomas Arnold, Walter Hook, William Hale, William Bright, Herbert Kelly, Roland Allen, F. R. Barry, Mervyn Stockwood, John Robinson, Lesslie Newbigin and E. R. Wickham. Factors influencing the development of the idea at each successive phase are identified, the most salient of which are: pressure for each local community to be self-sufficient in ministry, for the Church to offer ministry in a style and expression congruent with working-class culture, for the removal of the divide between clergy and laity, for the Church to offer meaningful witness in 'the world of work', and for supplementary ordained assistance for the diminishing numbers of stipendiary clergy. But throughout the period examined, constant restraints are shown to have been operating, restricting the smooth development of the idea. Chief amongst these are the protective reactions of the clerical profession and the over-riding influence of the parochial system. Finally, particular structural factors inhibiting the development of ministry in secular employment are identified.